Structure-sensitive elastography: on the viscoelastic powerlaw behavior of in vivo human tissue in health and disease - Sack, Ingolf; Jhrens, Korinna; Wrfel, Jens; Braun, Jrgen (Soft matter, 2013)
Elastography combines medical imaging with soft tissue mechanics and is used for the diagnosis of diseases associated with an altered stiffness of affected tissue. Beyond stiffness, dynamic elastography can measure viscoelastic constants sensitive to the network structure of polymers or biological materials. In this article current applications of in vivo multifrequency magnetic resonance elastography to healthy or diseased tissue are revisited in order to develop a unified framework for the interpretation of disease-related structural changes using viscoelastic powerlaw constants. The generalized view on different organs and processes such as liver fibrosis, neuronal tissue degradation, and muscle contraction reveals systematic signatures of the underlying microstructural changes to viscoelastic powerlaw constants. It is shown that in vivo powerlaw constants measured by elastography scale the mechanical properties of cellular networks into the macroscopic images obtained by magnetic resonance imaging (MRI) or ultrasound. This sensitivity to scales far below image resolution makes dynamic elastography an ideal diagnostic tool for the assessment of subtle alterations in living tissue occult to other medical imaging methods. Elastography combines medical imaging with soft tissue mechanics and is used for the diagnosis of diseases associated with an altered stiffness of affected tissue.